Probing electron dynamics by IR+XUV pulses - Reinhard, Paul-Gerhard; Suraud, Éric (European Physical Journal D, 2020)
Abstract: By recording observables of electron emission we analyze the response of small metal clusters and organic molecules to a pump probe setup using an IR fs laser pulse as pump followed by an attosecond XUV pulse as probe. As tool for the study, we use Time Dependent Density Functional Theory (TDDFT) in real time complemented by a simple 2-level model for principle effects. As observables, we consider total ionization, average kinetic energy from Photo Electron Spectra (PES) and anisotropy parameters from Photo-electron Angular Distributions (PAD). We show that these signals can provide a map of the system’s dynamical properties. The connection is especially simple for metal clusters in which the response is dominated by the Mie surface plasmon. The case of organic molecules is more involved due to the considerable spectral fragmentation of the underlying dipole response. But at least the dipole anisotropy from PAD provides a clean and robust signal which can be directly associated to system’s properties even reproducing non-linear effects such as the change of spectra with excitation strength. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-08-14